Ambidextrous leadership, customer orientation, environmental innovation to improve service innovation capability through digital capabilities and technological capabilities as mediating variables in Umkm in Berau District, East Kalimantan - Hasnawati; Kusumaningtyas, Amiartuti; Cempena, Ida Bagus (Edelweiss Applied Science and Technology, 2024)
Berau District is in the northern part of East Kalimantan Province and borders directly with North Kalimantan Province. As of 2014, the administrative territory of Berau District was divided into 13 districts with a total of 100 villages and 10 villages. Micro, Small and Medium Enterprises (MSMEs) are economic drivers in Berau district that are still faced with classical problems such as infrastructure, licensing, marketing, distribution and financing as well as post- 19 recovery processes. In connection with the problem, to build micro, small enterprises, and corporations, it is necessary to support the healthy real sector to combat poverty through the strengthening of the purchasing power of better society and the help of financing with light interest. The purpose of this research. Based on the background and the formula of the problems that have been outlined earlier, then the purpose of this research is to develop a model of the conceptual framework by means of proof and analysis; (1). The impact of ambidextrous leadership on digital capabilities on MSME perpetrators in Berau district (2), the impact of customer orientation on digital capacity on MSE perpetrator in Beru district (3), the effect of environmental innovation on digital Capabilities in MSE Perpetrator in Berau district (4). The effect of digital capability on technological capacities in the UMKM Perpetrant in Berea district (5), the influence of digital capacities on service innovation capability in UMM Perpetrator at Beraus district (6). The total sample that meets the criteria in this study is 353 samples and is processed using SmartPLS data processing. The results of this study indicate that there is a direct relationship between the impact of Ambidextrous Leadership, Customer Orientation, Environmental Innovation on Service Innovation Capability.